Large-area plastic nanogap electronics enabled by adhesion lithography - Semple, J; Georgiadou, D; Wyatt-Moon, G; Yoon, M; Seitkhan, A; Yengel, E; Rossbauer, S; Bottacchi, F; McLachlan, M; Bradley, D; Anthopoulos, T (Nature Publishing Group, 2018)
Large-area manufacturing of flexible nanoscale electronics has long been sought by the printed electronics industry. However, the lack of a robust, reliable, high throughput and low-cost technique that is capable of delivering high-performance functional devices has hitherto hindered commercial exploitation. Herein we report on the extensive range of capabilities presented by adhesion lithography (a-Lith), an innovative patterning technique for the fabrication of coplanar nanogap electrodes with arbitrarily large aspect ratio. We use this technique to fabricate a plethora of nanoscale electronic devices based on symmetric and asymmetric coplanar electrodes separated by a nanogap ≺ 15 nm. We show that functional devices including self-aligned-gate transistors, radio frequency diodes and rectifying circuits, multi-colour organic light-emitting nanodiodes and multilevel non-volatile memory devices, can be fabricated in a facile manner with minimum process complexity on a range of substrates. The compatibility of the formed nanogap electrodes with a wide range of solution processable semiconductors and substrate materials renders a-Lith highly attractive for the manufacturing of large-area nanoscale opto/electronics on arbitrary size and shape substrates.